Pengembangan Model Evaluasi Pembelajaran Berbasis Online pada Mata Pelajaran Pendidikan Agama Islam di SD Negeri 3 Sekongkang - Edy Susanto (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
Development of Online-Based Learning Evaluation Models in Islamic Religious Education Subjects in Sekongkang 3 Elementary School, this study aims to find out the improvement in the quality and motivation of student learning in Islamic Religious Education subjects in class V of Sekongkang 3 Elementary School in odd semester 2019 / 2020. Based on the results of the study found that 1). There is an increase in the quality of student learning, the improvement can be seen in increasing the value obtained by students in grade V after the use of an online-based assessment system (Repeat) in Islamic Religious Education Subjects; 2). The use of online-based questions and assessment applications on Islamic religious education subjects also increases student motivation in activities during the learning process, in addition, the use of this application is also able to reduce student time in working on questions during the assessment process.